2020
DOI: 10.1111/ejn.14665
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the ventral tegmental area evokes sleep‐like state transitions under urethane anaesthesia in the rat medial prefrontal cortex via dopamine D1‐like receptors

Abstract: The role of dopamine in regulating sleep‐state transitions during, both natural sleep and under anaesthesia, is still unclear. Recording in vivo in the rat mPFC under urethane anaesthesia, we observed predominantly slow wave activity (SWA) of <1 Hz in the local field potential interrupted by occasional spontaneous transitions to a low‐amplitude‐fast (LAF) pattern of activity. During periods of SWA, transitions to LAF activity could be rapidly and consistently evoked by electrical stimulation of the ventral teg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
0
11
0
2
Order By: Relevance
“…In line with our results, D -amphetamine increases the release of both NE and DA ( Kuczenski and Segal, 1997 ; Rothman et al, 2001 ) and has been shown to accelerate emergence from anesthesia via DA receptors ( Taylor et al, 2013 ; Kenny et al, 2015 ). Furthermore, activation of DA neurons in the ventral tegmental area is known to induce an Up state-like depolarization in PFC pyramidal neurons ( Lewis and O’donnell, 2000 ; Onn and Wang, 2005 ; Iwashita, 2014 ; Gretenkord et al, 2020 ), accelerate emergence from anesthesia ( Solt et al, 2014 ; Taylor et al, 2016 ), and promote wakefulness ( Eban-Rothschild et al, 2016 ; Oishi et al, 2017a ; Sun et al, 2017 ). Additional evidence suggests that DA produces these effects, at least in part, via D1 and D2-like receptors in the nucleus accumbens ( Eban-Rothschild et al, 2016 ; Oishi et al, 2017b ; Luo et al, 2018 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, D -amphetamine increases the release of both NE and DA ( Kuczenski and Segal, 1997 ; Rothman et al, 2001 ) and has been shown to accelerate emergence from anesthesia via DA receptors ( Taylor et al, 2013 ; Kenny et al, 2015 ). Furthermore, activation of DA neurons in the ventral tegmental area is known to induce an Up state-like depolarization in PFC pyramidal neurons ( Lewis and O’donnell, 2000 ; Onn and Wang, 2005 ; Iwashita, 2014 ; Gretenkord et al, 2020 ), accelerate emergence from anesthesia ( Solt et al, 2014 ; Taylor et al, 2016 ), and promote wakefulness ( Eban-Rothschild et al, 2016 ; Oishi et al, 2017a ; Sun et al, 2017 ). Additional evidence suggests that DA produces these effects, at least in part, via D1 and D2-like receptors in the nucleus accumbens ( Eban-Rothschild et al, 2016 ; Oishi et al, 2017b ; Luo et al, 2018 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…What's more, electrical stimulation of VTA continuously eliminates slow‐wave activity (SWA) and induces low amplitude rapid (LAF) network rhythm, similar to REMs. Systemic infusion of D1‐like receptors antagonist inhibited the effects of VTA stimulation in all mPFC subregions, implying that DA mediates the shift from SWA to REM‐like state induced by VTA stimulation through D1‐like receptors 36 …”
Section: The Role Of D1rs and D2rs In General Anesthesiamentioning
confidence: 95%
“…Systemic infusion of D1-like receptors antagonist inhibited the effects of VTA stimulation in all mPFC subregions, implying that DA mediates the shift from SWA to REM-like state induced by VTA stimulation through D1-like receptors. 36 In another study, microinjecting D1R agonist or antagonist facilitated or delayed the awakening from isoflurane anesthesia in young mice by activating or inhibiting D1Rs in the NAc shell, respectively. Nonetheless, this modulation capacity of D1Rs in the NAc shell declined in aged mice.…”
Section: The Role Of D1rs and D2rs In General Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Nosso grupo (Ruggiero et al, 2018; (Morales & Margolis, 2017). A transição é marcada pela alteração na dinâmica oscilatória do PFC regulada por receptores dopaminérgicos D 1 , e é observada também durante sono natural (Gretenkord et al, 2019). Também foi mostrado que a depleção aguda de dopamina suprime parcialmente o sono de ondas lentas e totalmente o sono REM, sendo este último recuperado pela injeção sistêmica de agonistas de receptores dopaminérgicos D 2 , mas não D 1 .…”
Section: Sincronia Hipocampo-córtex Pré-frontalunclassified